Le conflit frontalier sino-soviétique de 1969 - Hervouet, Gérard (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1979)
The Sino-Soviet conflict of 1969 constitutes part of an historical conflictual continuity between China and the Soviet Union. Three distinct phases have been delimited in this conflict. The approach employed makes it possible to give proper emphasis to the most critical period, that in which the greatest incompatibility in the stated objectives of the two parties occurred. Clearly, the apprehensions of the two States were formulated in terms of perception which enables due consideration of the systemic stakes of the crisis, the territorial aspect of which remained marginal. The density and the types of interaction identified throughout the conflict show the conflict's evolution with precision. As a complement to the application of the comparative analysis of conflict model, the search for domestic factors that could have been determinants of the origins of the border incidents enables a fuller understanding of this crisis.